2015
DOI: 10.1590/s1984-29612015065
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of antibodies anti -Toxoplasma gondii, Neospora caninum and Leptospira interrogans in a captive deer herd in Southern Brazil

Abstract: A large number of Brazilian zoos keep many endangered species of deer, however, very few disease surveillance studies have been conducted among captive cervids. Blood samples from 32 Brazilian deer (Blastocerus dichotomus, Mazama nana and Mazama americana) kept in captivity at Bela Vista Biological Sanctuary (Foz do Iguaçu, Brazil) were investigated for 10 ruminant pathogens, with the aims of monitoring deer health status and evaluating any potential zoonotic risk. Deer serum samples were tested for Brucella a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
4
2
Order By: Relevance
“…In other studies, the most detected serovars in wild deer were L. Grippotyphosa and L. Pomona, which have small rodents and pigs as their main hosts, respectively [74][75][76][77]. However, in the present study, the serovar Hardjo was detected with a higher frequency than that observed in other cervids species in LAC countries: (i) 5.6% in white-tailed deer in Mexico [78]; (ii) 0% in pampas deer in Argentina [61]; (iii) 0% in gray brocket deer in Bolivia [62]; and (iv) in mash deer, sambar deer, and pampas deer in Brazil (0-11.9%) [64,[79][80][81]. The exposure to this serovar is similar to the highest rate reported in other regions of the world such as in elk (Cervus elaphus), mule deer (Odocoileus hemionus), white-tailed deer, and moose (Alces alces) in North America (0-11%) [77,[82][83][84][85][86][87], and in red deer, fallow deer (Dama dama), and roe deer (Capreolus capreolus) in Europe (0-10.5%) [74,[88][89][90].…”
Section: Leptospira Interroganscontrasting
confidence: 69%
See 1 more Smart Citation
“…In other studies, the most detected serovars in wild deer were L. Grippotyphosa and L. Pomona, which have small rodents and pigs as their main hosts, respectively [74][75][76][77]. However, in the present study, the serovar Hardjo was detected with a higher frequency than that observed in other cervids species in LAC countries: (i) 5.6% in white-tailed deer in Mexico [78]; (ii) 0% in pampas deer in Argentina [61]; (iii) 0% in gray brocket deer in Bolivia [62]; and (iv) in mash deer, sambar deer, and pampas deer in Brazil (0-11.9%) [64,[79][80][81]. The exposure to this serovar is similar to the highest rate reported in other regions of the world such as in elk (Cervus elaphus), mule deer (Odocoileus hemionus), white-tailed deer, and moose (Alces alces) in North America (0-11%) [77,[82][83][84][85][86][87], and in red deer, fallow deer (Dama dama), and roe deer (Capreolus capreolus) in Europe (0-10.5%) [74,[88][89][90].…”
Section: Leptospira Interroganscontrasting
confidence: 69%
“…However, other studies propose that pestiviruses could be enzootic to wild cervid populations and thus maintained independently of livestock [98,100,103]. There are few studies focusing on detecting antibodies against pestiviruses in wild cervids in other LAC countries; until now, all animals were seronegative [61,62,81].…”
Section: Pestivirusmentioning
confidence: 99%
“…BVDV is a well-known immunosuppressant and an important cause of bovine respiratory disease [ 123 126 ]. Diagnosis of BVDV has been attempted without success in South American deer species [ 18 , 127 ]; nevertheless, seropositivity was detected in Colombian WTD [ 128 ]. In cattle, M .…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples from 32 cervids (22  M. nana , dwarf brocket deer; 4  M. americana , red brocket deer and 6 B. dichotomus , marsh deer) that were previously surveyed for other pathogens [16, 17] were included in this study. The animals were maintained in captivity at Bela Vista Biological Sanctuary, Itaipu Binational Dam, in Foz do Iguaçú, Paraná State, Brazil (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, all animals tested negative for Brucella abortus , bovine viral diarrhea virus, foot-and-mouth disease virus, infectious bovine rhinotracheitis, Eastern equine encephalitis, Western equine encephalitis and Venezuelan equine encephalitis [17]. This monitoring has provided important information for animal and public health and for conservation purposes, given that internationally, Brazilian dwarf brocket deer, marsh deer and red brocket deer have been considered vulnerable [1820].…”
Section: Introductionmentioning
confidence: 99%